Membangun Internet Sehat Dengan Mikrotik - Wendra Jumaisarki (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
The development of the digital world and technology plays an active role in everyday human life and activities. The use of the digital world and technology pr ovides a lot of information so that it can be accessed easily so that it is not uncommon for the use of technology to be used for things that are not good, such as accessing sites that contain negative content. Not everyone knows how to filter sites that contain negative content, so a system is needed that can filter sites that contain negative content. This study aims to build a system that can filter sites on the internet so that healthy internet use can be applied. The sites are filtered using a proxy web proxy. The data was collected by means of literature study, system design, topology design, and filter application. Testing of blocked sites using a browser. The results of this research are web proxies can block sites such as URLs, websites, keywords, and the download process of a file. A web proxy cannot block some sites with a specific domain. Filtering with a web proxy takes a long time because of the many configurations required.